Influence of antioxidant additives on the spectral characteristics in the visible of olive and soybean oils - Truyols, M.; Thomas, J. (Ars Pharmaceutica (Internet), 1967)
A study has been made with two vegetable oils of the changes wich their visible spectral characteristics undergo after heating with food, both with and without additives. The differences found in these characteristics are expressed for the case of each additive; in general the antioxidant acts as a conserving agent of the colour. No significant influence of the additive on the polyunsaturated acid content has been found.